2006
DOI: 10.1007/s11270-006-9242-7
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Chromate into Calcium Carbonate Structure During Coprecipitation

Abstract: To rigorously assess treatment technologies and establish regulatory framework for chromatecontaminated site remediation, it is useful to know the exact chromium speciation in soil matrices. In an earlier study, Thornton, E. C., & Amonette, J. E. (1999). Hydrogen sulfide gas treatment of Cr(VI)-contaminated sediment samples from a plating-waste disposal siteimplications for in-situ remediation. Environmental Science & Technology, 33, 4096-4101, reported that some chromate in the bulk particles was not accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 20 publications
6
53
0
Order By: Relevance
“…Chen, Okudan & Riley (2010) found that CaCO 3 produced by Proteus mirabilis had an unusual morphology and structure, mainly formed by vaterite spheres. CaCO 3 precipitation by a mixture of Ca 2+ and CO 3 -2 involves three steps as follows: 1) amorphous calcium carbonate formation with low stability and solubility, 2) their transformation into vaterite, and 3) obtaining calcite which is the most stable solid state of CaCO 3 (Hua, Deng, Thornton, Yang & Amonette, 2007;Shen et al, 2006;Spanos & Koutsoukos, 1998;Wei, Shen, Zhao, Wang & Xu, 2003).…”
Section: Calcium Carbonate Crystalsmentioning
confidence: 99%
“…Chen, Okudan & Riley (2010) found that CaCO 3 produced by Proteus mirabilis had an unusual morphology and structure, mainly formed by vaterite spheres. CaCO 3 precipitation by a mixture of Ca 2+ and CO 3 -2 involves three steps as follows: 1) amorphous calcium carbonate formation with low stability and solubility, 2) their transformation into vaterite, and 3) obtaining calcite which is the most stable solid state of CaCO 3 (Hua, Deng, Thornton, Yang & Amonette, 2007;Shen et al, 2006;Spanos & Koutsoukos, 1998;Wei, Shen, Zhao, Wang & Xu, 2003).…”
Section: Calcium Carbonate Crystalsmentioning
confidence: 99%
“…In contrast, the reductive capacity of Portland cement measured by the Cr(VI) method was an order of magnitude higher than that measured by the Ce(IV) method. This result could be attributed to the precipitation of Cr-bearing phases or coprecipitation of Cr(VI) with CaCO 3 formed at alkaline pH during the reaction with Portland cement powder with the bicarbonate buffer solution used in the Cr(VI) method (Hua et al 2007;Tang et al 2007). The removal of Cr(VI) by such precipitation mechanism, rather than the "pure" reduction of Cr(VI) to Cr(III), results in overestimated reductive capacity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reductive capacity of Portland cement measured by the Cr(VI) method was 0.349 meq/g, which was an order of magnitude higher than the reductive capacity measured by the Ce(IV) method. This high reductive capacity of Portland cement determined by the Cr(VI) method could result from the coprecipitation of Cr(VI) with CaCO 3 formed at alkaline pH during the 7-day reaction with Portland cement powder (Hua et al 2007;Tang et al 2007), not from the reduction of Cr(VI) to Cr(III) only. A previous study also reported that Cr-bearing phases such as CaCrO 4 and CaCrO 4 •2H 2 O were formed at alkaline pH (10.5-12.2) during the reaction of Portland cement with high-Cr-concentration solution (15,000-50,000 mg/L) (Laforest and Duchesne 2005), suggesting that the high reductive capacity of Portland cement determined by the Cr(VI) method could be overestimated by the precipitation of Cr-bearing phases.…”
Section: Reductive Capacity Of Dry Ingredientsmentioning
confidence: 95%
“…The formation of CaCO3 templates with embedded Tinuvin 1130 and Tinuvin 292 was obtained by the coprecipitation (Figure 3) of CaCl2 and Na2CO3 salts [20]. CaCO3 templates were prepared by mixing equal volume of Na2CO3 (1 M) and CaCl2 (1 M) solutions under magnetic stirring for 1 h. 0.1 g of concentrated commercial solution of Tinuvin 1130 or Tinuvin 292 was added to the CaCl2 solution prior to the mixing with the Na2CO3 solution.…”
Section: Synthesis Of Caco3 Templates With Tinuvin 1130 and Tinuvin 292mentioning
confidence: 99%